Building the Relationship Quality Model: An Investigation of the Chemical Industry - Andreas Samudro; Ujang Sumarwan; Megawati Simanjuntak; Eva Z Yusuf (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
The purpose of this study is to develop a relationship quality model and investigate the links among the constructs. This empirical study aims to explore the construct's links between the key constituents of relationship quality model: trust, satisfaction, and commitment. The Structural Equation Model is employed to confirm the model and investigate the correlations and influences between constructs. The results of the analysis confirm the direct influence of commitment toward loyalty. Satisfaction does not have a direct influence on loyalty, but through commitment as a mediate variable. The finding confirms the relationship quality model with strong influences among constituents: satisfaction, trust and commitment; Commitment is the only variable whose direct influence toward customer loyalty.